Catalytic Aromatization of Propane-Butane Fractions over Polyfunctional Zeolite Catalysts: Effect of Process Parameters - Nurzhan Nurgaliyev; Nur-Sultan Mussa; Seitkhan Azat; Rachid Amrousse; Kainaubek Toshtay (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
The catalytic conversion of a propane–butane fraction into aromatic hydrocarbons was investigated over ZnLaFe/ZSM-5 and phosphorus-modified ZnLaFeP/ZSM-5 catalysts. The catalysts were characterized by N₂ adsorption–desorption, X-ray diffraction, SEM-EDX, TEM, NH₃-TPD, TGA and FTIR-pyridine analyses. Textural and structural studies confirmed the preservation of the MFI framework after metal and phosphorus incorporation, while acidity measurements revealed that phosphorus modification significantly reduced the concentration of medium-strong and strong Brønsted acid sites, leading to a moderated acid strength distribution. Catalytic performance tests demonstrated that ZnLaFe/ZSM-5 exhibits high PBF conversion over a wide temperature range, whereas ZnLaFeP/ZSM-5 delivers substantially higher aromatic yields, reaching up to 59.7% at 550 °C and a gas hourly space velocity (GHSV) of 350 h⁻¹. The enhanced aromatization performance of the phosphorus-containing catalyst is attributed to the synergistic interaction between moderated Brønsted acidity and Zn–phosphate Lewis acid sites, which promote dehydrogenation, cyclization, and aromatization while suppressing excessive cracking and coke formation. Stability tests over 11 h confirmed the superior resistance of ZnLaFeP/ZSM-5 to deactivation, with only minor losses in conversion and aromatic yield and a stable product distribution dominated by benzene and toluene. Pilot-scale experiments using larger catalyst beds (100 and 500 mL) further demonstrated that the optimized acidity and catalytic functionality are retained upon scale-up. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).